Clinical efficacy of immunoglobulin on the treatment of severe fever with thrombocytopenia syndrome: a retrospective cohort studyResearch in context - Shan-Shan Zhang; Juan Du; Ning Cui; Xin Yang; Lan Zhang; Wan-Xue Zhang; Ming Yue; Yong-Xiang Wu; Tong Yang; Xiao-Ai Zhang; Zhen-Dong Yang; Hong-Di Lv; et al. (EBioMedicine, 2023)
Summary: Background: Optimal treatment strategy for severe fever with thrombocytopenia syndrome (SFTS) remained unknown. We aimed to evaluate the efficacy of intravenous immunoglobulin (IVIG) on SFTS. Methods: A retrospective cohort study was conducted based on medical records of the laboratory-confirmed SFTS patients hospitalized during 2010–2020 in the 154th hospital, China. A 1:1 propensity score matching with age, sex, the interval from symptom onset to admission, presence of chronic viral hepatitis, diabetes and disease severity was performed between Non-IVIG group (supportive therapy) and IVIG group (IVIG plus supportive therapy). The matching variables were adjusted to compare the case fatality rates (CFRs), viral load and laboratory parameters between the two groups. Risk ratio (RR) and 95% confidence interval (CI) were reported. Findings: Totally 2219 SFTS patients were recruited. CFRs were significantly higher in 1051 patients in IVIG group than 1168 patients in Non-IVIG group (19.0% vs. 4.6%, RR = 4.30, 95% CI 3.12–5.93). The difference remained significant after matching (17.2% vs. 5.1%, RR = 4.02, 95% CI 2.71–5.97). The CFR of IVIG group was significantly higher in all age groups, two IVIG therapy delay groups and two therapy duration groups compared to that of Non-IVIG group (all P < 0.05). IVIG therapy was related to higher viral loads and reduced counts of lymphocytes, T cells, CD4+ T cells and natural killer cells in the blood (all P < 0.05). Interpretation: No obvious efficacy of IVIG in saving life or improving outcome of SFTS was observed. Caution is needed for clinical physicians to continue prescribing IVIG for SFTS patients. Funding: Natural Science Foundation of China.